2020
DOI: 10.1186/s40486-020-00113-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polymers to enhance mechanical properties of microneedles for bio-medical applications

Abstract: To pierce through the skin and interact with the first biofluid available, microneedles should be mechanically strong. However, some polymers used to fabricate microneedles yield insufficient strength for the fabrication of arrays (PDMS, highly porous structures, etc.). To enhance mechanical properties, piercing materials can be used. They aim to pierce the skin evenly and dissolve quickly, clearing the way for underlying microneedles to interact with the interstitial fluid (ISF). Three materials-carboxymethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…If some polymers have insufficient piercing abilities, piercing materials can be used in conjunction with the MNs themselves. For example, one study used hyaluronic acid, carboxymethyl cellulose and alginate as a piercing material to pierce the skin quickly (through quick dissolution) and evenly, thereby allowing underlying MNs to interact with interstitial fluid [ 181 ]. This study found that a sharp needle tip and overall mechanical strength were the two most important factors affecting needle insertion.…”
Section: Parameters Affecting Mn Insertionmentioning
confidence: 99%
“…If some polymers have insufficient piercing abilities, piercing materials can be used in conjunction with the MNs themselves. For example, one study used hyaluronic acid, carboxymethyl cellulose and alginate as a piercing material to pierce the skin quickly (through quick dissolution) and evenly, thereby allowing underlying MNs to interact with interstitial fluid [ 181 ]. This study found that a sharp needle tip and overall mechanical strength were the two most important factors affecting needle insertion.…”
Section: Parameters Affecting Mn Insertionmentioning
confidence: 99%
“…The height and base diameters were reduced by approximately 5.08% and 7.32% in the INL MNs compared to the silicon MNs ( Figure 2 ) and 14.19% and 1.74% for BA MNs compared to the purchased molds’ specifications. Differences in height and base diameters between master molds and polymer MNs are common due to the dehydration of the polymer and have been reported for different dissolvable, swellable and biodegradable polymers [ 50 , 51 ]. For instance, Demir et al used pyramidal-shaped MN (900 µm height and 250 µm base diameter) and six polymers to produce MNs.…”
Section: Resultsmentioning
confidence: 99%
“…GwenaëlBonfante et al discussed three materials-carboxymethyl cellulose (CMC), alginate, and hyaluronic acid (HA)-for the manufacture of microneedles. However, the microneedles have been designed with low concentrations for rapid dissolution while maintaining the strengthening effect and were used varying from 1 to 5% (w/w) in deionized water [138]. Their overall performance aspects, such as geometric parameters (width, height, and tip width), piercing capabilities, and dissolution time, are measured and discussed.…”
Section: Sodium Alginate (Sa)-based Microneedlementioning
confidence: 99%